Indonesian avian influenza viruses character in second wave epidemic - Dharmayanti, N.L.P.I.; Indriani, R; Damayanti, R; Wiyono, A; Adjid, R.M.A. (Indonesian Journal of Animal and Veterinary Sciences, 2005)
Second wave of epidemic avian influenza occurred from December 2004 until April 2005. In March 2005, the disease had infected some districts in South Sulawesi such as Wajo and Sopeng. More than 21 field isolates have been collected and identified as avian influenza virus subtype H5N1. In this study further characterized was undertaken for 14 isolates of avian influenza using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) and sequencing in region of HA1 gene. It was then followed by genetic analysis to identify the mutation and phylogenetic relationship of the isolates. The study indicates that the Indonesia isolates collected in second wave epidemic are generally having a different group to the isolates group in 2003 and 2004. There is point mutation in the nucleotide sequence of the isolate collected at August 2004-March 2005, that is the replacement of adenine by guanine in the position of 195. Â  Â  Key Words: Avian Influenza Virus, Second Epidemic Wave, Mutation